De Novo or inherited: gonosomal mosaicism in hereditary angioedema due to C1 inhibitor deficiency - Batlle-Masó, Laura; Perurena-Prieto, Janire; Viñas-Giménez, Laura; Aguiló-Cucurull, Aina; Fernández-Álvarez, Paula; Gil-Serrano, Johana; Guilarte, Mar; Colobran, Roger (Frontiers in Immunology, 2025)
Hereditary angioedema (HAE) is a rare genetic disease, characterized by transient and self-limiting episodes of subcutaneous or submucosal swelling that spontaneously resolve within two to five days. The most common form of HAE, HAE-C1-INH, is caused by deleterious mutations in the SERPING1 gene, encoding the C1-Inhibitor protein, and its diagnosis is confirmed by decreased C1-INH function. Distinctively from other genetic forms of HAE, up to 15-20% of HAE-C1-INH cases are sporadic caused by de novo mutations. Here, we report a patient with apparently sporadic HAE-C1-INH. The patient had compatible clinical symptoms and a markedly low C1-INH function, and the parents showed normal values of C4 and normal C1-INH function. In the patient, we identified a novel splice site mutation in SERPING1 (c.890-1G>C) and, by cDNA analysis, we confirmed its pathogenicity. Despite normal C1-INH function in the parents, we found that the mother was, unexpectedly, a mutation carrier. The inverted profile of the Sanger peaks compared with the patient, strongly suggested the presence of gonosomal mosaicism in the mother. We confirmed and quantified the mosaicism in different tissues by high depth NGS-based deep amplicon sequencing, showing a similar frequency of the variant ranging from 17 to 23%. In this study, we present the first case of gonosomal mosaicism in a family with a single child affected with HAE-C1-INH from unaffected parents. Our results underscore the importance of parental genetic testing in all patients, regardless of whether the parents are affected, and highlights the implications of gonosomal mosaicism for genetic counseling.